Liming and quality of guava fruit cultivated in Brazil - Prado, R. D.; Natale, W.; da Silva, JAA (Elsevier B.V., 2005)
An experiment was conducted on guava trees Psidium guajava L. (cv. Paluma) grown in the Experimental Citrus Culture Station of Bebedouro, SP, on dystrophic, acid Typical Hapludox in order to assess the effects of application of increasing lime doses to the soil on the quality of guava fruits on the basis of the physicochemical changes observed in the fruits after harvesting. The treatments consisted of increasing lime doses applied before planting, considering 0, 1.85, 3.79, 5.56 and 7.41 t ha(-1), applied in August 1999. Leaf calcium content was assessed at flowering time. After fruit harvesting, calcium content in the pulp, total weight, transverse diameter, length, pulp weight, % pulp, Brix degrees (degrees Brix), titratable acidity, and fruit ratio were determined. Loss of fruit fresh mass, firmness and color were determined daily during a period of 8 days of storage. Lime application to an acid Red Latosol before guava tree planting did not affect the physical characteristics of the fruits but provided a lower loss of fresh matter and greater fruit firmness when the fruits presented Ca levels close to 0.99 g kg(-1). It is important to conduct new studies of the effects of liming on guava fruit quality under different edaphic-climatic conditions and on different guava tree genotypes. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: Psidium guajava; fruit; calcium; liming; post-harvest; quality